2021
DOI: 10.1136/bmjopen-2020-048575
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for hyperhomocysteinemia: a population-based cross-sectional study from Hunan, China

Abstract: ObjectivesHyperhomocysteinemia is an independent risk factor for cardiovascular diseases. We aimed to investigate the prevalence and risk factors for hyperhomocysteinemia, especially modifiable lifestyle factors, such as smoking behaviour and dietary factors.DesignPopulation-based cross-sectional study.SettingHunan Province, ChinaParticipantsA total of 4012 participants completed the study, between July 2013 and March 2014. The median age is 55 (interquartile range: 45–63) years, with 1644 males (41%) and 2368… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
4
1
Order By: Relevance
“…Hyperhomocysteinemia is a significant contributor to cardiovascular and cerebrovascular illnesses, with meta-analysis revealing a rising trend in hyperhomocysteinemia prevalence in China, currently at 37.2%. 23 Previous population-based studies conducted in Guangxi and Hunan have shown that the prevalence of homocysteine was 50.8% and 35.4%, respectively, 24 , 25 both exceeding the 26.87% reported in the present study. The prevalence of homocysteine might vary due to factors such as region and population.…”
Section: Discussioncontrasting
confidence: 63%
“…Hyperhomocysteinemia is a significant contributor to cardiovascular and cerebrovascular illnesses, with meta-analysis revealing a rising trend in hyperhomocysteinemia prevalence in China, currently at 37.2%. 23 Previous population-based studies conducted in Guangxi and Hunan have shown that the prevalence of homocysteine was 50.8% and 35.4%, respectively, 24 , 25 both exceeding the 26.87% reported in the present study. The prevalence of homocysteine might vary due to factors such as region and population.…”
Section: Discussioncontrasting
confidence: 63%
“…BNs outperforms Logistic regression in risk factor detection. Firstly, combined with previous study using Logistic regression for factors associated with hyperhomocysteinemia 18 and our comparison between the two models in the Result, BNs facilitates new ideas for disease relationship study and allows for the influencing factors of a certain intermediate link in the occurrence and development of HHcy. Secondly, BNs could offer more valuable information, as it’s represented by “population clustering” we mentioned in the result.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, Logistic regression was employed to explore risk factors for HHcy 18 , 19 , suggesting that age, BMI, smoking, diet, total cholesterol levels and sex are significantly associated with HHcy. Yet, the model comes with some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HHcy was reported to be one of the risk factors in young intracranial large-artery atherosclerotic stroke patients [ 10 ]. Although a number of studies on the risk factors of HHcy have been reported in middle-aged or older populations [ 11 ], the distribution profile of plasma Hcy levels and the risk factors of HHcy among young adults have not drawn much attention.…”
Section: Introductionmentioning
confidence: 99%